An alternative palliative surgical method for advanced malignant obstructive jaundice: Laparoscopic bridge choledochoduodenostomy - Lianyuan, Tao; Hongsheng, Xiao; Xuxiang, Zou; Liancai, Wang; Dazhao, Lei; Deyu, Li (Frontiers in Surgery, 2023)
Background: This study introduces an alternative palliative surgical procedure called laparoscopic bridge choledochoduodenostomy (LBCDD) for patients with advanced malignant obstructive jaundice (AMOJ). Methods: Patients with AMOJ who had LBCDD between January 2017 and August 2020 were identified from databases of two institutions in China. Results: A total of 35 patients (male 12; female 23) with an average age of 64 (±10.65) years were enrolled. The average dimeter of tumor is 4.24 (±1.11) cm. All patients undertook LBCDD within an average operation time of 75 (±31) min with a mean blood loss of 32(±14) ml. One patient had controlled bile leakage after the operation and two developed surgical site infection involving the epigastric orifices. All of them were solved by conservative treatment. All patients were discharged smoothly after an average hospital stay of 5.5 days, and no conversion to open surgery was required. Conclusions: LBCDD is a safe and efficient palliative surgery, which has a good therapeutic effect on patients with AMOJ.